FINDING LIST OF BLUE STARS IN THE NORTH GALACTIC POLE II - IRIARTE ERRO, B; CHAVIRA, E (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1956)
We present a list of 772 new blue stars found in the direction of the North Galactic Pole. The field is of 500 square degrees.
BOL OBS TONAN TACUB
Keywords: FINDING LIST, BLUE STARS, NORTH GALACTIC, POLE II; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS